Xanthohumol, a Prenylated Flavonoid from Hops (Humulus lupulus), Prevents Platelet Activation in Human Platelets. (7th May 2012) - Lee, Ye-Ming; Hsieh, Kuo-Hsien; Lu, Wan-Jung; Chou, Hsiu-Chu; Chou, Duen-Suey; Lien, Li-Ming; Sheu, Joen-Rong; Lin, Kuan-Hung
Abstract : Xanthohumol is the principal prenylated flavonoid in the hop plant ( Humulus lupulus L.). Xanthohumol was found to be a very potent cancer chemopreventive agent through regulation of diverse mechanisms. However, no data are available concerning the effects of xanthohumol on platelet activation. The aim of this paper was to examine the antiplatelet effect of xanthohumol in washed human platelets. In the present paper, xanthohumol exhibited more-potent activity in inhibiting platelet aggregation stimulated by collagen. Xanthohumol inhibited platelet activation accompanied by relative [Ca 2+ ] i mobilization, thromboxane A2 formation, hydroxyl radical (OH ● ) formation, and phospholipase C (PLC) γ 2, protein kinase C (PKC), mitogen-activated protein kinase (MAPK), and Akt phosphorylation. Neither SQ22536, an inhibitor of adenylate cyclase, nor ODQ, an inhibitor of guanylate cyclase, reversed the xanthohumol-mediated inhibitory effect on platelet aggregation. Furthermore, xanthohumol did not significantly increase nitrate formation in platelets. This study demonstrates for the first time that xanthohumol possesses potent antiplatelet activity which may initially inhibit the PI3-kinase/Akt, p38 MAPK, and PLC γ 2-PKC cascades, followed by inhibition of the thromboxane A2 formation, thereby leading to inhibition of [Ca 2+ ] i and finally inhibition of platelet aggregation. Therefore, this novel role of xanthohumol may represent a high therapeutic potential for treatment or prevention of cardiovascular diseases.